Unveiling Pagodroma Nivea's Fossil Healing Power: A Journey Through Farmacoantarctic Chronicles And Bioactivity Studies - Yuneka Saristiana; Yunita Dian Permatasari; Anita Dwi Setyarini; Hasriyani, Hasriyani; Neni Probosiwi; Fendy Prasetyawan (Paspama Institute, 2024)
Research on the bioactivity of Antarctic organisms has garnered significant attention due to the continent's unique environmental conditions and the potential therapeutic value of its inhabitants. This study delves into the bioactivity of Pagodroma nivea, commonly known as the Snow Petrel, found in Antarctica, aiming to explore its medicinal potential. Despite previous research highlighting the bioactivity of various organisms in extreme environments, specific investigations into Pagodroma nivea remain scarce. Farmacoantarctic Research offers a promising avenue for exploring the therapeutic properties of Antarctic organisms, including Pagodroma nivea, traditionally used for medicinal purposes by local communities. Understanding the biochemical adaptations of organisms to Antarctica's extreme conditions is crucial, as these adaptations may yield bioactive compounds with pharmacological potential. The research not only seeks to uncover the bioactivity of Pagodroma nivea but also aims to contribute to drug development and environmental conservation efforts. In a parallel discussion, the study examines Mumijo, a traditional remedy found in various regions, including Antarctica. Chemical analysis of Mumijo extract, particularly the ester wax fraction, reveals its potential biomedical applications, including wound healing, skin diseases, and neuroprotection. The presence of glycerol-related ethers in Antarctic Mumijo suggests further avenues for exploration in neuroprotection and antimicrobial properties. By investigating the bioactivity of Antarctic organisms like Pagodroma nivea and Mumijo, this research offers insights into their therapeutic potential and underscores the importance of conservation efforts to preserve these unique ecosystems.